Breeding and Reproductive Health Profiles in Pet Canine Females - Panchal, Mahesh T.; Patel, Jagdish A.; Chaudhari, Dinesh V.; Bhanderi, Bharat B. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The reproductive health and breeding status was studied in 124 pet dogs (121 females, 3 males) presented at the Veterinary Clinical Complex of the College of Veterinary Science and A.H. Anand. It comprised a majority of Labradors (32.26%), followed by German Shepherds (16.13%), Pomeranians (12.90%), Mongrels (10.48%), Pugs (9.68%), and others. Body condition-wise, 10.48% bitches were fatty, 68.55% normal, 13.71% below average, and 7.26% were debilitated. All three males were conditioned enough. Among 121 bitches, 53 were nulliparous, 27 primiparous, 32 pluriparous, and 9 were of unknown parity. Out of 124 dogs examined, 117 (94.36%) were free from ectoparasites, whereas 7 (5.64%) had ticks’ infestation. Among the 121 bitches, 69.42% were cyclic, 13.22% acyclic, and 17.36% with unknown status. Expression of behavioural proestrus and estrus was intense and noticeable in 66.95%, subtle in 27.27% and unknown in 5.79% bitches. Reaction by the bitch to the dog was reported to be poor/refractory, good/amicable and ferocious in 9, 57 and 9 bitches, respectively. Clinical reproductive entities (207) included the pregnancy failure (16.43%) to be the highest, followed by pregnancy (12.56%), proestrus (11.11%), open pyometra (7.73%), seeking counselling (7.25%), misalliance (5.80%), vaginal tumours (4.83%), pseudopregnancy (4.35%), close pyometra (1.93%) and others. Ten (83.33%) genital discharge samples from 12 bitches having open pyometra yielded bacterial isolates with Corynebacterum spp. being the predominant and most isolates were sensitive to Amikacin, Chloramphenicol, Gentamicin, while resistant to Ampicillin.